The effects of Pilates training on respiratory muscle strength in patients with ankylosing spondylitis - Yentur, Songul Baglan; Sarac, Devrim Can; Sari, Fulden; Tore, Gizem; Salman, Reyhan Bilici; Ozturk, Mehmet Akif; Oskay, Deran (Taylor & Francis Inc, 2024)
Background Reduction in flexibility and mobility are important factors that lead to impairments in quality of life, reduction of exercise tolerance, and a decreased pulmonary capacity with the progression of Ankylosing Spondylitis (AS). Aim The purpose of this study was to investigate the effects of Pilates exercises on mobility, quality of life, and respiratory muscle strength in patients with AS. Methods Forty patients with AS were randomly divided into two groups as Pilates group and the control group. The Pilates group performed Pilates exercises in supervised group sessions and the control group performed conventional exercises at home three days a week for eight weeks. The main outcome measure was respiratory muscle strength. Secondary outcome measures were forced vital capacity (FVC), forced expiratory volume in one second (FEV1) FEV1/FVC ratio, chest expansion, Bath indices (BASDAI, BASMI), Ankylosing Spondylitis Quality of Life Questionnaire (ASQoL) and six-minute walk test (6MWT). All participants were assessed by a blind assessor at baseline and the end of eight weeks. Results Thirty-six AS patients (n = 19 in the Pilates group, n = 17 in the control group) completed the study. Respiratory muscle strength, FEV1/FVC, chest expansion, BASDAI, BASMI, ASQoL, and 6MWT significantly improved at the 8(th) week (p < .05) in the Pilates group, while inspiratory muscle strength, FEV1/FVC, chest expansion, and 6MWT showed significant improvements in the control group at 8(th) week compared to baseline (p < .05). No significant between-group differences were observed when the change over time values were compared (Delta). Conclusion Both Pilates and home exercises seem to be effective for improving respiratory parameters and functional status in patients with AS. Pilates exercises without using any equipment and additional exercises is found to be useful for improving respiratory functions and disease-related symptoms.
Keywords: Ankylosing Spondylitis; Pilates exercises; respiratory muscle strength